The Influence of Applying the Think Pair Share and Cooperative Script Cooperative Learning Models on Economics Learning Achievement in View of Students' Learning Motivation - Tatik Romita; Olaide Sekinat Opeloyeru (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to compare the effect of learning models (Think Pair Share and Cooperative Script) on student learning achievement. Also researched was the influence of learning motivation (high, medium, low) on students' economic learning achievement. The research involves the interaction between learning models and students' learning motivation on economic learning achievement. Methodology: This research method is a quasi-experiment with a population of class X high school students. The sample consists of two classes selected using saturated sampling techniques. The experimental class applies Think Pair Share, while the control class uses Cooperative Script. Learning achievement data is collected through tests, while student learning motivation data is collected through questionnaires. Hypothesis analysis used two-way ANOVA with a 3 x 2 factorial design using SPSS 21. Main Findings: The results of the research show that: there are differences in the influence of the think pair share and cooperative script cooperative learning models on student learning achievement (Fcount = 11.939, and p < 0.05); 2) there are differences in the influence of high, medium and low learning motivation on students' economic learning achievement (Fcount of 22.463 and p < 0.05); 3) there is an interaction between the learning model and student learning motivation on the economic learning achievement of class students (Fcount of 3.787 and p < 0.05). Novelty/Originality of this study: This research provides a new contribution in comparing the influence of the Think Pair Share (TPS) and Cooperative Script cooperative learning models on students' economic learning achievement. The research results show that the TPS learning model has a more significant influence on increasing students' economic learning achievement and learning motivation.